2016
DOI: 10.1016/j.jtcme.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Obstetrics and gynecology outpatient scenario of an Indian homeopathic hospital: A prospective, research-targeted study

Abstract: The authors aimed to document prescriptions and clinical outcomes in routine homeopathic practice to short list promising areas of targeted research and efficacy trials of homeopathy in obstetrics and gynecology (O&G).Three homeopathic physicians participated in methodical data collection over a 3-month period in the O&G outpatient setting of The Calcutta Homeopathic Medical College and Hospital, West Bengal, India. A specifically designed Excel spreadsheet was used to record data on consecutive appointments, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…37 Nowadays, it is used worldwide in many clinical settings with positive results. [38][39][40][41][42] Results of a survey of German menopausal women showed that homeopathy was one of the three most popular Complementary & Alternative Medicine (CAM) interventions (14.9%), after changes in lifestyle (28.7%) and St. John's wort (18.3%). The women perceived homeopathy as very useful (73.7%) in managing their symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…37 Nowadays, it is used worldwide in many clinical settings with positive results. [38][39][40][41][42] Results of a survey of German menopausal women showed that homeopathy was one of the three most popular Complementary & Alternative Medicine (CAM) interventions (14.9%), after changes in lifestyle (28.7%) and St. John's wort (18.3%). The women perceived homeopathy as very useful (73.7%) in managing their symptoms.…”
Section: Introductionmentioning
confidence: 99%